2015
DOI: 10.2527/jas.2015-9378
|View full text |Cite
|
Sign up to set email alerts
|

Tissue expression analysis, cloning, and characterization of the 5′-regulatory region of the bovine fatty acid binding protein 4 gene1

Abstract: Fatty acid binding protein 4 (FABP4) is a member of the FABP family of proteins that bind fatty acids and play important roles in fatty acid uptake and intracellular transport. In the present study, we cloned the 5'-regulatory region of bovine and identified its transcription initiation sites. Sequence comparative analysis demonstrated amino acids and promoter sequences of were highly conservative in mammals. Real-time PCR analysis revealed the products of bovine were very highly expressed in subcutaneous adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…In mammals, the core promoter has generally been identified near the transcription initiation site (28)(29) . For example, the core promoter of cattle (Bos taurus) fabp4 was present in the region of 272 bp upstream from the initiation codon (30) . The distinctive location of the T. ovatus fabp4 core promoter region indicated that there may be distinct regulatory mechanisms of fabp4 between T. ovatus and mammals.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the core promoter has generally been identified near the transcription initiation site (28)(29) . For example, the core promoter of cattle (Bos taurus) fabp4 was present in the region of 272 bp upstream from the initiation codon (30) . The distinctive location of the T. ovatus fabp4 core promoter region indicated that there may be distinct regulatory mechanisms of fabp4 between T. ovatus and mammals.…”
Section: Discussionmentioning
confidence: 99%
“…After differentiation of the C2C12 myoblasts into myotubes for 7 days, we prepared nuclear protein extracts as previously described [ 21 , 23 ]. We incubated probes of a 200 fmol of 5'-biotin labeled MYOG (or C/EBPß) with 10μg nuclear extracts of C2C12 myotubes (or 10μg3T3-L1nuclear extracts), 2μl 10×binding buffer, 1μl 50% Glycerol, 1μl MgCl2 and 1μl poly (dI.dC) in a volume of 20 μl.…”
Section: Methodsmentioning
confidence: 99%
“…The pGL3-basic vector was used as the external control. At 5 h after transfection, the media was replaced by DMEM with 2 % horse serum (HS) (Gibco-Invitrogen, Carlsbad, CA, USA) to induce differentiation of C2C12 myoblasts to myotubes for 40 h. At 45 h after transfection, the cells were lysed and analysed with a dual-luciferase reporter assay according to the manufacturer's instructions [25,26].…”
Section: Real-time Pcr Analysis Of Spatial Expression Patternmentioning
confidence: 99%
“…The PCR primers (FABP3-GSP1 and FABP3-GSP2, Supplemental Table 1) were adopted to acquire the 5 0 -end of the FABP3 gene. Reaction conditions were performed in the first PCR as described previously [25,26]. The second PCR template was a 20-fold dilution of the first PCR products.…”
Section: Molecular Cloning and Sequence Analysismentioning
confidence: 99%